Travel Photography Sebagai Media Promosi Desa Wisata Silokek - Aziz Fauzi Rahmat; Melisa Fitri Rahmadinata; Fauziah Sri Andria Hafid (Journal of Tourism Sciences, Technology and Industry, 2023)
Photography is a method of producing images using light as the main composition. Photography is currently not only a medium for recording images for documentation, but is also developing as a medium for promoting goods, services and tourist destinations. Its use as a promotional media for tourist destinations is currently considered more efficient, because through attractive photos it can attract tourists to visit these tourist destinations, one of which is the Silokek tourist village. Silokek Tourism Village is one of the tourist villages that has been registered in the Indonesian Tourism Village Award event. The charm of tourism in the Silokek Tourism Village is packed with documentation through travel photography so that people are more familiar with the beauty of the Silokek tourist village.